Tracking phosphorus security: indicators of phosphorus vulnerability in the global food system - Cordell, Dana; White, Stuart (Food security, 2015)
Phosphorus underpins global food systems by ensuring soil fertility, farmer livelihoods, agricultural productivity and global food security. Yet there is a lack of research and effective governance at global or national scales designed to ensure the future availability and accessibility of this global resource. The world’s main source of phosphorus, phosphate rock, is a finite resource that is becoming increasingly scarce, expensive and subject to geopolitical tensions as one country, Morocco, controls three-quarters of the world’s remaining high-grade reserves. Given the criticality of phosphorus and the vulnerability of the world’s food systems to phosphorus scarcity, there is a strong need to stimulate appropriate sustainable phosphorus practices and technologies, and simultaneously, to initiate effective international governance mechanisms, including policy/research coordination and accountability. Sustainability indicators are increasingly being used as tools to facilitate accountability, implementation, evaluation and communication for global sustainability challenges. This paper presents the first comprehensive set of phosphorus vulnerability and security indicators at global and national scales. Global indicators include: phosphate price, market concentration and supply risk, relative physical phosphorus scarcity and eutrophication potential. National indicators include: farmer phosphorus vulnerability, national phosphorus vulnerability, national phosphorus equity and soil phosphorus legacy. Monitoring and tracking such indicators at the national and global levels can ultimately provide evidence of key phosphorus vulnerabilities or ‘hotspots’ in the food system, support effective phosphorus governance to stimulate targeted and effective action, raise awareness of this food security challenge, and evaluate the effectiveness and performance of global or national sustainable phosphorus projects.